A new fuzzy version of Euler's method for solving differential equations with fuzzy initial values - Muhammad Zaini, Ahmad; M. K., Hasan (Universiti Kebangsaan Malaysia (UKM), 2011)
Link to publisher's homepage at http://www.ukm.my/